Why Humean Causation Is Extrinsic. (20th May 2019) - Pallies, Daniel
Abstract : According to a view that goes by "Humeanism, " causal facts supervene on patterns of worldly entities. The simplest form of Humeanism is the constant conjunction theory: a particular type‐ F thing causes a particular type‐ G thing iff (i) that type‐ F is conjoined with that type‐ G thing and (ii) all F 's are conjoined with G 's. The constant conjunction theory implies that all causation is extrinsic, in the following sense: for all positive causal facts pertaining to each possible region, it's extrinsic to that region that those causal facts pertain to it. Actual Humeans don't accept the constant conjunction theory; they accept more sophisticated versions of Humeanism. But I argue that they, too, are committed to the thesis that all causation is extrinsic. In arguing for this claim, I use a discussion from Brian Weatherson as a springboard. Weatherson argues that on a plausible Humean view, some regions are such that all of their possible duplicates have the same or similar natural laws. I show that this is false. If Humeanism is true, then for every possible region, there are possible duplicates of that region with utterly alien natural laws. As a consequence, no causal facts pertain intrinsically to any region.